2014
DOI: 10.1155/2014/819847
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress Response in Granulocytes from Older Patients with a Hip Fracture May Account for Slow Regeneration

Abstract: Proximal femur fracture, a typical fracture of the elderly, is often associated with morbidity, reduced quality of life, impaired physical function and increased mortality. There exists evidence that responses of the hematopoietic microenvironment to fractures change with age. Therefore, we investigated oxidative stress markers and oxidative stress-related MAPK activation in granulocytes from the young and the elderly with and without fractured long bones. Lipid peroxidation levels were increased in the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Chemiluminescent signals were detected with a CCD camera. Signal intensities were determined by densitometry using the ImageJ software (NIH, Bethesda, USA) and normalized to the corresponding GAPDH signals (Wang et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Chemiluminescent signals were detected with a CCD camera. Signal intensities were determined by densitometry using the ImageJ software (NIH, Bethesda, USA) and normalized to the corresponding GAPDH signals (Wang et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that BMSCs injected into fracture sites are confronted with its apoptosis within a few days on account of harsh microenvironment conditions with oxidative stress, which is a state of imbalance between reactibe oxygen species (ROS) generation and intracellular antioxidants, resulting in cellular damage, and eventually leading to cell death (11)(12)(13). Therefore, strategies to protect the implantation of BMSCs from apoptosis and to improve their survivability in oxidative stress are therapeutically attractive in MSC-based therapy for delayed union, nonunion and persistent bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been an increase in TBARS values in patients with fractures, this increase was not statistically significant ( Figure 3). Wang and colleagues also showed an increase in this parameter in elderly patients with femoral neck fractures (2). In their study, they investigated the value of TBARS in younger patients with femur fractures and have obtained results that show a statistically significant increase unlike those observed in elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…It transfers the body weight from the pelvic bone to the shinbone (1). Femur fractures are a significant cause of morbidity and mortality among the locomotor apparatus injuries, especially in the elderly population (2). Although any part of this bone can break, the femoral neck or hip is the most common part to fracture (3).…”
Section: Introductionmentioning
confidence: 99%